Long-Term Use of Tamoxifen Is Associated With a Decreased Subsequent Meningioma Risk in Patients With Breast Cancer: A Nationwide Population-Based Cohort Study - Sun, Li-Min; Lin, Cheng-Li; Sun, Sean; Hsu, Chung Y.; Shae, Zonyin; Kao, Chia-Hung (Frontiers in Pharmacology, 2019)
Background: Earlier studies have indicated a relatively higher risk of occurring meningioma among female breast cancer survivors and have suggested that tamoxifen might decrease this risk. The present study evaluated whether tamoxifen use in breast cancer patients can reduce the risk of meningioma. Methods: We designed a population-based cohort study by using data from the National Health Insurance system of Taiwan to assess this issue. Between January 1, 2000 and December 31, 2008, women with breast cancer and of age ≥20 years were included. They were divided into 2 groups: those who had not received tamoxifen therapy and those who had. The Cox’s proportion hazard regression analysis was conducted to estimate the effects of tamoxifen treatment and the subsequent meningioma risk. Results: We identified a total of 50,442 tamoxifen users and 30,929 non-tamoxifen users. Tamoxifen users had a borderline significantly lower overall risk of meningioma than non-tamoxifen users [adjusted hazard ratio (aHR) = 0.64, 95% confidence interval (95% CI) = 0.40–1.02]. A statistically significant difference was found in those patients with tamoxifen treatment duration longer than 1500 days (aHR = 0.42, 95% CI = 0.19–0.91) or with cumulative dosage exceeding 26320 mg (aHR = 0.44, 95% CI = 0.22–0.88). Furthermore, no statistically significant joint effect of aromatase inhibitors and tamoxifen on the occurrence of meningioma among breast cancer patients was seen. Conclusion: Tamoxifen users had a non-significantly (36%) lower risk of developing meningioma than did tamoxifen non-users; however, our data indicated that tamoxifen therapy is associated with a reduced meningioma risk for Taiwanese breast cancer patients receiving long duration or high cumulative dosage treatment with tamoxifen.